Tax Spillovers under Separate Accounting and Formula Apportionment. - Søren Bo Nielsen; Pascalis Raimondos-Møller; Guttorm Schjelderup (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
It is observed in the real world that taxes matter for location decisions and that multinationals shift profits by transfer pricing. The US and Canada use Formula Apportionment (FA) to tax corporate income, and the EU is debating a switch from Separate Accounting (SA) to FA. This paper develops a theoretical model that compares basic properties of FA to SA. The focal point of the analysis is on how changes in tax rates affect capital formation, input choice, and transfer pricing as well as spillovers on tax revenue in other countries. The analysis shows that a move from SA to FA will not eliminate such spillovers and will, in cases identified in the paper, actually aggravate them.
Keywords: 330